Mistakes in the usage of anatomical terminology in clinical practice - Kachlik, David; Bozdechova, Ivana; Cech, Pavel; Musil, Vladimir; Baca, Vaclav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2009)
BACKGROUND: Anatomical terminology serves as a basic communication tool in all the medical fields. Therefore Latin anatomical nomenclature has been repetitively issued and revised from 1895 (Basiliensia Nomina Anatomica) until 1998, when the last version was approved and published as the Terminologia Anatomica (International Anatomical Terminology) by the Federative Committee on Anatomical Terminology. METHODS AND RESULTS: A brief history of the terminology and nomenclature development is mentioned, along with the concept and contributions of the Terminologia Anatomica including the employed abbreviations. Examples of obsolete anatomical terms and their current synonyms are listed. Clinicians entered the process of the nomenclature revision and this aspect is demonstrated with several examples of terms used in clinical fields only, some already incorporated in the Terminologia Anatomica and a few obsolete terms still alive in non-theoretical communication. Frequent mistakes in grammar and orthography are stated as well. CONCLUSION: Authors of the article strongly recommend the use of the recent revision of the Latin anatomical nomenclature both in theoretical and clinical medicine.
Keywords: Anatomy; anatomie; terminologie jako téma; lidé; Terminology as Topic; Humans